Measuring GPU-accelerated parallel SVM performance using large datasets for multi-class machine learning problem - Sulaiman M.A.H.B.; Suliman A.; Ahmad A.R. (Institute of Electrical and Electronics Engineers Inc., 2023)
Artificial intelligence; Computer graphics; Computer graphics equipment; Data mining; Learning systems; Parallel processing systems; Program processors; Quadratic programming; Computational time; GPU-accelerated; Graphics Processing Unit; Machine learning problem; Performance measurements; Real-time forecasting; Support vector machine (SVMs); Viable solutions; Support vector machines